2018
DOI: 10.1371/journal.pgen.1007200
|View full text |Cite
|
Sign up to set email alerts
|

Exome-wide somatic mutation characterization of small bowel adenocarcinoma

Abstract: Small bowel adenocarcinoma (SBA) is an aggressive disease with limited treatment options. Despite previous studies, its molecular genetic background has remained somewhat elusive. To comprehensively characterize the mutational landscape of this tumor type, and to identify possible targets of treatment, we conducted the first large exome sequencing study on a population-based set of SBA samples from all three small bowel segments. Archival tissue from 106 primary tumors with appropriate clinical information wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
97
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 64 publications
18
97
2
Order By: Relevance
“…53 A similar finding was found in an analysis of 106 cases in which 11 (10.4%) patients had BRAF mutations but none were BRAF V600E. 61 Distinct differences also exist for ERBB2. Despite a similar rate of ERBB2 alterations between SBA and gastric cancer (9.5% for both), the rate of amplification differs greatly, with only 23% of alterations being amplification in SBA compared with 69% in gastric cancer.…”
Section: Molecular Alterationssupporting
confidence: 62%
See 1 more Smart Citation
“…53 A similar finding was found in an analysis of 106 cases in which 11 (10.4%) patients had BRAF mutations but none were BRAF V600E. 61 Distinct differences also exist for ERBB2. Despite a similar rate of ERBB2 alterations between SBA and gastric cancer (9.5% for both), the rate of amplification differs greatly, with only 23% of alterations being amplification in SBA compared with 69% in gastric cancer.…”
Section: Molecular Alterationssupporting
confidence: 62%
“…This finding is similar to 3 other studies, which report 70% to 76% of the ERBB2 genomic alterations were mutations. [60][61][62] Studies have reported high rates of MSI-H or dMMR in SBA, with a rate of 21.6% in an 83-patient series 60 and 14.2% in a 106-patient series. 61 However, these rates are highly influenced by the stage distribution of the population, with higher rates seen in earlier-stage disease.…”
Section: Molecular Alterationsmentioning
confidence: 99%
“…Comprehensive exome and whole-genome sequencing efforts have identified SBNET as mutationally "quiet" compared to other solid neoplasms with 0.1 variants per 10 6 nucleotides, which are mostly transitions (a point mutation in which a purine is changed to the other purine or a pyrimidine to the another) [43]. For comparison, in SB adenocarcinoma the median mutational burden is approximately 3.96 mutations per 10 6 nucleotides [44], comparable to colorectal and gastric carcinoma [45,46]. Sequencing of tumours from 50 individuals with SBNET identified 1,230 genes with somatic mutations; however, 90% were only present in single individuals.…”
Section: Genetic and Epigenetic Landscape Of Sbnetmentioning
confidence: 99%
“…But there is also research demonstrated that acvr1b suppressed early stages of pancreatic tumorigenesis [28]. In small-bowel adenocarcinoma, exome-wide somatic mutation characterization identified acvr1b and acvr2a as novel candidate driver genes [29]. In prostate cancer cells acvr1b promoted lymph node metastasis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of ACVR1B is a primary cause of autosomal-dominant vascular dysplasia syndrome [25], while increase of ACVR1B induces blood vessel branching [26]. In cancer studies, there are several researches showing different roles of ACVR1B based on different cancer types, such as tumor-suppressor role in pancreatic cancer [27,28], oncogenic roles in small-bowel adenocarcinoma [29], prostate cancer [30], and leukemia [31]. To our knowledge, there is no functional study of ACVR1B in GC.…”
Section: Introductionmentioning
confidence: 99%